Principals' Opinion Towards Inclusion of Chinese Language in School Curriculum: A Case of Primary Schools in Nigeria - Okafor, Miracle Uzochukwu; Shaoan, Md Mirajur Rhaman; Arif, Muhammad; Jamil, Bushra; Irfan, Saida; Lahinta, Ayu Novianti (Journal of Teaching and Learning, 2026)
The study explores the opinions of school principals, who are pivotal in curriculum implementation, towards the inclusion of the Chinese language in the Nigerian primary school curriculum. A qualitative methodology was employed, involving semi-structured interviews with 10 public school principals from southeastern Nigeria. This study employs Sociocultural Theory, and the SWOT model was used to identify the strengths, weaknesses, opportunities, and threats. Findings revealed mixed reactions of both convergence in support for the initiative, and divergence in concerns about implementation and educational priorities. The majority of participants in this study expressed support, citing global relevance, cognitive benefits, and future opportunities for students. However, challenges such as finding qualified teachers, the complexity of the Chinese language, developing an integrated curriculum, and ensuring adequate resources were noted. The study emphasizes that addressing these challenges will require careful planning, substantial investment, and a balanced approach that considers both global and local linguistic priorities.